PENGARUH TEKNIK RELAKSASI PERNAFASAN TERHADAP DERAJAT NYERI PADA IBU BERSALIN KALA I DI PUSKESMAS KETAPANG II SAMPIT TAHUN 2019 - hardianti aprina (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2022)
ABSTRACT Background : Breathing relaxation techniques a way to reduce labor pain non-pharmacologically. Based on 2017 IDHS 259-305/100,000 live births. Cause of AKI a labor trauma due labor pain. The results preliminary study at Ketapang II Sampit Public Health Center in 2019, most women experienced labor pain, measured by pain rating scale. The study found : Knowing Effect Breathing Relaxation Technique on Degree of Pain in Mother Giving Birth First Period at Ketapang II Sampit Public Health Center in 2019. Metode Research : The study pre-experimental method, one group pretest-posttest design. Conducted at Ketapang II Sampit Public Health Center March-July 2019, sample 10 people, accidental sampling technique from primary data. Independent variable breathing relaxation technique, dependent variable degree of pain in mother giving birth first period. Study population is mother giving birth first period in Ketapang II Sampit Public Health Center in 2019. The result : Of 10 respondents before and after intervention, before intervention majority experienced severe pain, 6 people (60%), after intervention there decrease in pain levels, majority experienced moderate pain, 5 people (50%). Based on the "Test Statistics" output the Asymp value is known. Sig. (2-tailed) is worth 0.008, where 0.008 <0.05. Conclusion : There difference the degree of pretest and posttest, can concluded that is influence breathing relaxation techniques on degree of pain in mother giving birth first period at Ketapang II Sampit Public Health Center in 2019.